A Case Study of Emotional Impact Through Effective Three Act Structure: “Spirited Away - Chai, Jing Chin (Universiti Malaysia Sarawak (UNIMAS), 2017)
Storytelling is one of the important elements in making a successful animation to drive the emotions of the audiences. Thus, this research is aimed to analyse the three act structure storytelling technique based on the animation of Spirited Away by Hayao Miyazaki. The objective of this research is to observe the story flow and conflicts in the animation of Spirited Away. This research was conducted by observing and analysed the data from the conflicts in Spirited Away. This research could be used as a reference or useful guideline for future study about storytelling technique.